Reproductive biology of Palaemon pandaliformis (Stimpson, 1871) (Crustacea, Decapoda, Caridea) from two estuaries in southeastern Brazil - Mortari, Rafael Campaneli [UNESP]; Nunes Pralon, Bruno Gabriel [UNESP]; Negreiros-Fransozo, Maria Lucia [UNESP] (Int Science Services/balaban Publishers, 2009)
The reproductive biology of Palaemon pandaliformis was investigated in the estuaries of the Comprido and Ubatumirim rivers at Ubatuba, State of São Paulo, Brazil, by means of samples obtained from April 2003 to March 2004. Samples were collected monthly, using sieves, which were passed several times under the marginal vegetation. In the laboratory, the sex of each shrimp was assessed and the carapace length (CL, mm) measured. Ovigerous females were separated and Counted for determination of fecundity. The egg diameter was measured with a calibrated micrometer scale under an stereo-microscope. The breeding period was seasonal in the Comprido River Estuary, and continuous throughout the year in the Ubatumirim River estuary. The mean size of ovigerous females was higher in the population in the Comprido River (5.90 +/- 0.68 mm CL +/- sd) than in the Ubatumirim River (5.50 +/- 0.58 mm). The most intense reproductive period of P. pandaliformis was from October 2003 to March 2004 for both estuaries. The mean fecundity of P. pandaliformis in the Comprido River was 189 +/- 53 eggs (n = 124), and at Ubatumirim, 130 +/- 25; mean +/- sd eggs (n=80), values that are similar to other palaemonid species from similar latitudes. A positive correlation between the number of eggs and the size of the female was obtained for both populations. The eggs were relatively small, indicative of low energy allocation to each embryo, with mean dimensions ranging from 0.44 +/- 0.08 mm to 0.69 +/- 0.069 mm.
Keywords: Palaemonidae; reproduction; reproductive period; fecundity; egg volume